A note on specification testing in some structural regression models - Walter Beckert (Centre for Microdata Methods and Practice (cemmap), 2019)
There exists a useful framework for jointly implementing Durbin-Wu-Hausman exogeneity and Sargan-Hansen overidenti cation tests, as a single arti cial regression. This note sets out the framework for linear models and discusses its extension to non-linear models. It also provides an empirical example and some Monte Carlo results.
Keywords: C21; C26; C36; 330; endogeneity; identification; testing; artificial regression